EPEN-18. Oncogenic 3D genome conformations identify novel therapeutic targets in ependymoma. (3rd June 2022) - Okonechnikov, Konstantin; Camgöz, Aylin; Park, Donglim Esther; Chapman, Owen; Hübner, Jens-Martin; Jenseit, Anne; Chakraborty, Abhijit; Pagadala, Meghana; Bump, Rosalind; Chandran, Sahaana; Kraft, Katherina; Hidalgo, Rocio Acuna; et al.
Abstract: Ependymoma (EPN) is an aggressive pediatric tumor that occurs throughout the central nervous system. The two most aggressive molecular subgroups of EPN are the supratentorial ZFTA-fusion associated group (ST-EPN-ZFTA) and the posterior fossa group A (PF-EPN-A). Although the molecular characteristics underlying the tumorigenesis of these subgroups have been extensively studied, these tumors remain difficult to treat. Hence, innovative therapeutic approaches are urgently needed. Here, we used genome-wide chromosome conformation capture (Hi-C), complemented with CTCF (insulators) and H3K27ac (active enhancers) ChIP-seq, as well as gene expression and whole-genome DNA methylation profiling in primary and relapsed EPN tumors and cell lines, to identify chromosomal rearrangements and regulatory mechanisms underlying aberrant expression of genes that are essential for EPN tumorigenesis. By integrating these heterogenous data types, we have observed the formation of new topologically associated domains ('neo-TADs') caused by intra- and inter-chromosomal structural variants in both tumors. In addition, we observed 3D chromatin complexes of regulatory elements, and the replacement of CTCF insulators by DNA hyper-methylation in PF-EPN-A tumors. These tumor-specific 3D genome conformations can be associated with the transcriptional upregulation of nearby genes. Through inhibition experiments we validated that these newly identified genes, including RCOR2, ITGA6, LAMC1, and ARL4C, are highly essential for the survival of patient-derived EPN cell lines in a disease subgroup-specific manner. Thus, our study identifies novel potential therapeutic vulnerabilities in EPN and extends our ability to reveal tumor-dependency genes and pathways by oncogenic 3D genome conformations even in tumors that lack known genetic alterations.